Holistic Education through Bil Hikmah Communication: A Review of Surah Luqman verses 12-19 - Bildan, Bildan Muhammad Sya'ban; aulia, muhammad hizba; Ridwan, Ahmad Dimyati; Muzakki, Rifqi Fathan Saepudin; Ali, M.Mauris Faruqi; Nazhan, Faiz Aswa; Rafilah, Nabila Hasna (TA`DIBUNA, 2025)
This study aims to analyze the implementation of holistic education through bil hikmah communication in building the character of the younger generation in this context, namely students, based on thematic studies of the Qur'an, especially Q.S. Luqman verses 12-19. The era of disruption brings new challenges in character building, so a relevant and holistic approach based on Islamic values is needed. This research uses a descriptive qualitative approach and literature method with content analysis techniques to examine the values of bil hikmah communication contained in the Qur'an and Hadith. The results show that the main values such as tawhid, responsibility, emotional intelligence, patience, tolerance, love of peace, as well as communication ethics, are important elements in holistic education. The integration of these values supports character education that is more adaptive, spiritual, and relevant to the challenges of the digital era, both in formal and non-formal education environments. This research is expected to be a guide for educators and parents in shaping a noble generation through the bil hikmah communication approach sourced from the Qur'an and Hadith